Sikap Konsumen terhadap Pelayanan Pusat Kuliner Belut Godean Sleman Yogyakarta - Edy Rismiyanto; Totok Danangdjojo (Jurnal Maksipreneur, 2016)
Tourism industry growing rapidly nowadays is in culinary field which relates to food and beverage supply. The tourist trend recently is visiting a destination to look for or hunt for the local special food and do not hesitate to pay in high price to enjoy the cuisine. Special culinary tour of Yogyakarta becomes one of the tourism attractions of Special Region of Yogyakarta that be able to get great benefits toward community economy. Eel culinary business is potential to grow the local society economy.The aim of the research is to find out consumer attitude toward service center of Eel culinary at Godean Sleman Yogyakarta. Data collection technique used is questionnaire and sampling method used convenient sampling method.As for the research steps consisted of: 1) preparation step of the research instrument included literature review, research design setting and earlier observation, 2) step of data collection in the field is conducted by observation, questionnaire, interview, and secondary data collection, 3) step of data tabulation and analysis, consisted of: a) data component tabulation, including data reduction and data presentation, b) data verification including data validity, c) data analysis, using attitude index analysis method, 4) step of report writing as the final step of the research, where all results analyzed was presented in a structured written product. From the analysis using attitude index was obtained a value of 8,71 means the consumers have neutral attitude toward the service center of Eel culinary at Godean Sleman Yogyakarta. As for the attributes the best responded were access, credibility and tangible (parking are), and the worst responded attribute was (religious service).